Enhancing Mathematics Fluency: Comparing the Spacing of Practice Sessions With the Number of Opportunities to Respond. Issue 1 (1st March 2019) - Codding, Robin S.; Volpe, Robert J.; Martin, Ryan J.; Krebs, Genevieve
Abstract: The number of opportunities to respond (OTR) and spacing (massed or distributed practice) of practice sessions are important variables to consider in instructional design. The purpose of this pilot study was to compare the impact of these variables on trajectories of mathematics fluency. Second- and third-grade students ( N = 112) were randomly assigned to 1 of 4 conditions: (a) distributed practice, low OTR; (b) massed practice, low OTR; (c) distributed practice, high OTR; and (d) massed practice, high OTR. Students completed 1 practice session using cover-copy-compare for subtraction according to the group assignment. Multilevel modeling of 4 assessment time points (pretest, follow-up at 1, 4, and 7 days) was used to evaluate differences in retention (correct digits) between groups. After controlling for prior math knowledge, instructional level and OTR, but not spacing, were significant predictors of final score. These findings suggest that OTR is an important variable to consider when planning for instruction and intervention.